Brazil - Improving the Appraisal Framework for Road Transport Infrastructure Investments : Elements for Consideration - Véron, Adrien (World Bank, Washington, DC, 2014)
The main purpose of an appraisal framework for transport infrastructure projects and programs is to provide an objective and transparent basis for decision-makers to ascertain the feasibility and levels of priority of major transport projects and policies. An appraisal framework also serves a second, more general, purpose: to contribute to upgrading internal management processes aimed at improving the quality of expenditure. An adequate appraisal framework needs to: 1) strike a balance between an objective economic evaluation and a broader multi-criteria evaluation; and 2) provide clear methodologies and norms to guide appraisers, and ensure comparability among project appraisals, when time comes to prioritize the projects. To ensure that an appraisal framework can deliver on the two above-mentioned purposes, it is important to raise public awareness as to the basic principles and objectives of appraisals, and to structure public sector capacity to undertake or lead, as well as review appraisals, to ensure that they are reliable and of adequate quality. Appraisal frameworks are at different stages of development in different countries, with the most advanced frameworks. Brazil has made a lot of progress in that area since the end of the 1990s. Today, the legal framework is conducive to the systematic undertaking of appraisals. While progress has been made on structuring a series of norms and guidelines to allow for the implementation of the framework's directives, the normative body, overall, is still relatively vague and incomplete.